Evaluating the unconventional monetary policy of the bank of Japan: A DSGE approach - Rui Wang (Journal of Risk and Financial Management, 2021)
When the nominal interest rate reaches the zero lower bound (ZLB), a conventional monetary policy, namely, the adjustment of short-term interest rate, may become impractical and ineffective for central banks. Therefore, quantitative easing (QE) is one of the few available policy options of central banks for stimulating the economy and dealing with deflationary pressure. Since February 1999, the Bank of Japan (BoJ) has conducted several unconventional monetary policy programs. Considering the scarce research in this field from a structural macroeconomic model approach, a medium-scale New Keynesian DSGE model with government bonds of different maturities was developed to check the portfolio rebalancing channel of quantitative qualitative easing (QQE) conducted by the BoJ from April 2013 on the basis of the assumption of imperfect asset substitutability. The model was calibrated on the basis of the structure of the Japanese economy in April 2013. The main conclusion is that the BoJ's asset purchase has a real effect on pushing output and inflation higher, and long-term interest rates lower. Sensitivity simulation analysis shows that, given the same size of asset purchase, the persistence of asset purchase determines the peak effect in the short run. A long-lasting asset purchase can push up inflation higher, and long-term interest rates lower for a relatively longer period, but the long-run effect on output and investment does not have much difference. The policy implication for BoJ is just to announce a long-lasting QE program and make it credible to the market.
Keywords: E43; E44; E52; E58; 330; asset purchase; Bank of Japan; DSGE; quantitative easing; unconventional monetary policy